Elasticity of demand of major root and tuber crop in the rural forest zone: implications for research for development - Nkamleu, G.B.; Tchakoa, J.; Kenfack, J.P. (2010)
This paper analyses food consumption in rural households of forest zones. Based on a panel survey of 80 households in Cameroon, expenditure-elasticities of demand for roots and tubers are estimated and compared with those of other staples. Yam and cassava are the two most important root and tuber crops grown in Africa. The expenditure elasticity estimates for yam revealed that the domestic market potentials are high in forest zone for this crop, while in the case of cassava, it was established that the extent to which the potential market will be expanded, would depend on which degree the quality of the dry products can be improved